2019
DOI: 10.3389/fmicb.2019.02580
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Nitrite-Base Aerobic Denitrifying Bacterium Acinetobacter sp. YT03 and Its Transcriptome Analysis

Abstract: Nitrite in a water environment is very harmful to humans and aquatic animals. A novel aerobic denitrifying bacterium able to utilize NO2--N as the only nitrogen source was isolated for the purpose of removing nitrite from water, which was identified as Acinetobacter sp. and named as YT03. The growth and denitrification activity of strain YT03 was assessed comprehensively. Results showed that the nitrite in water with an initial concentration of 10 mg L–1 could be completely removed within 6 h by strain YT03, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…It has been reported that carbon source with a simple structure and low molecular weight might be more suitable for the growth of bacteria as well as for serving as electron donors during denitrification, as they could easily participate in simple biochemical pathways of carbon source utilization [ 27 , 28 ]. In agreement with previous studies [ 10 , 29 ], the current results also indicated that a higher NO 3 − -N removal efficiency of JD-014 was achieved when sodium succinate and sodium citrate were applied as the carbon source.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that carbon source with a simple structure and low molecular weight might be more suitable for the growth of bacteria as well as for serving as electron donors during denitrification, as they could easily participate in simple biochemical pathways of carbon source utilization [ 27 , 28 ]. In agreement with previous studies [ 10 , 29 ], the current results also indicated that a higher NO 3 − -N removal efficiency of JD-014 was achieved when sodium succinate and sodium citrate were applied as the carbon source.…”
Section: Resultsmentioning
confidence: 99%
“…Hence, the energy metabolism was improved with the addition of nitrate, which could induce more NADH and FADH 2 as electron donors to support the denitrification process. Moreover, it was reported that DctA was associated with the transport of succinate [ 27 ]. Herein, compared to the control without nitrate, the current results depicted that the dctA (GE00156)-encoding C 4 -dicarboxylate transporter was up-regulated 3.37- and 11.06-fold, respectively, in YE50 and YE300, indicating that the carbon metabolism of JD-014 was promoted during the aerobic denitrification with sodium succinate as a carbon source.…”
Section: Resultsmentioning
confidence: 99%
“…YT03 was reported to increase as the rotation speed increased. As the rotation speed was increased from 50 rpm to 250 rpm, the nitrogen removal rate reached the maximum value of 93.9% at 250 rpm (Li et al, 2019). The strain YC-34 showed a similar performance to Acinetobacter sp.…”
Section: Shaking Speedmentioning
confidence: 86%
“…The preserved strain Y-9 bacteria were activated in the LB medium at 150 rpm and 15°C for 36 h. Cells in the logarithmic growth phase were inoculated into a DM medium to assess the effects of the carbon source, C/N ratio, pH, and DO on Y-9–driven NO 3 – reduction ( Li et al, 2019 ; Yan et al, 2021 ).…”
Section: Methodsmentioning
confidence: 99%